Treatment Strategy According to Findings on Pressure-Flow Study for Women with Decreased Urinary Flow Rate - Yoshinori Tanaka; Naoya Masumori; Taiji Tsukamoto; Seiji Furuya; Ryoji Furuya; Hiroshi Ogura (Advances in Urology)
Purpose. In women who reported a weak urinary stream, the efficacy of treatment chosen according to the urodynamic findings on pressure-flow study was prospectively evaluated. Materials and Methods. Twelve female patients with maximum flow rates of 10 mL/sec or lower were analyzed in the present study. At baseline, all underwent pressure-flow study to determine the degree of bladder outlet obstruction (BOO) and status of detrusor contractility on Schäfer's diagram. Distigmine bromide, 10 mg/d, was given to the patients with detrusor underactivity (DUA) defined as weak/very weak contractility, whereas urethral dilatation was performed using a metal sound for those with BOO (linear passive urethral resistance relation 2–6). Treatment efficacy was evaluated using the International Prostate Symptom Score (IPSS), uroflowmetry, and measurement of postvoid residual urine volume. Some patients underwent pressure-flow study after treatment. Results. Urethral dilatation was performed for six patients with BOO, while distigmine bromide was given to the remaining six showing DUA without BOO. IPSS, QOL index, and the urinary flow rate were significantly improved in both groups after treatment. All four of the patients with BOO and one of the three with DUA but no BOO who underwent pressure-flow study after treatment showed decreased degrees of BOO and increased detrusor contractility, respectively. Conclusions. Both BOO and DUA cause a decreased urinary flow rate in women. In the short-term, urethral dilatation and distigmine bromide are efficacious for female patients with BOO and those with DUA, respectively.